Focus group study to identify the central facets of fear of hypoglycaemia in people with Type 2 diabetes mellitus. Issue 12 (9th October 2017) - Grammes, J.; Stock, W.; Mann, C. G.; Flynn, E. M.; Kubiak, T.
Abstract: Aims: To determine key worries about hypoglycaemia among insulin‐using adults with Type 2 diabetes using a focus group approach. Methods: Thirteen focus groups were conducted in three diabetes outpatient care units and one peer support group was set up, in Germany. A total of 64 insulin‐dependent adults with Type 2 diabetes (36.5% women, mean age 65.2 ± 11.0 years) discussed their worries about hypoglycaemia. The qualitative results were assigned into thematic categories using a bottom‐up coding procedure. Participants completed the Hypoglycaemia Fear Survey and demographic measures were recorded. The results of the Hypoglycaemia Fear Survey were contrasted with the focus group findings to evaluate how accurately the Hypoglycaemia Fear Survey comprehensively captures features of fear of hypoglycaemia in Type 2 diabetes. Results: Eight themes were identified: 'unconsciousness/death'; 'aloneness/ helplessness', 'fear of hurting somebody'; 'shame'; 'loss of physical control'; 'long‐term complications'; 'diabetes self‐management issues'; and 'impaired awareness'. A total of 30 participants (46.9%) scored ≥3 on at least one item of the Hypoglycaemia Fear Survey worry subscale, indicating elevated worries. The Hypoglycaemia Fear Survey comprehensively captured all identified themes. Self‐efficacy with regard to diabetes self‐management seemed to play an important role in fear of hypoglycaemia in Type 2 diabetes. Conclusions: Given that even subclinical worries can have negative effects on quality of life and diabetes self‐management, emphasis should be placed on diabetes education; in particular, to help patients to develop self‐efficacy concerning diabetes self‐management. The Hypoglycaemia Fear Survey comprehensively captures hypoglycaemia worries in Type 2 diabetes. Additional assessment of self‐efficacy might be beneficial to identify people at risk of developing hypoglycaemia worries. What's new?: Focus group discussions were conducted to get an insight into key worries and concerns about hypoglycaemia in insulin‐using adults with Type 2 diabetes ( n = 64). The themes identified were: unconsciousness/death; aloneness/helplessness; fear of hurting someone; shame, loss of physical control; long‐term complications; diabetes self‐management issues; and impaired awareness. Having hypoglycaemia while driving emerged as an important concern for the majority of participants of this study. Participants emphasized the positive effects of diabetes education to foster self‐efficacy and to reduce worry about hypoglycaemia. The Hypoglycaemia Fear Survey comprehensively captures hypoglycaemia‐related worries in Type 2 diabetes.